Long-term follow-up for efficacy and safety of treatment of retinitis pigmentosa with valproic acid. Issue 7 (20th April 2013) - Bhalla, Sheena; Joshi, Deval; Bhullar, Shaminder; Kasuga, Daniel; Park, Yeonhee; Kay, Christine N
Abstract : Aims: The purpose of this study was to determine the long-term efficacy and safety of valproic acid (VPA) treatment in patients with pigmentary retinal dystrophies. Methods: A retrospective chart review was conducted on 31 patients with a diagnosis of pigmentary retinal dystrophy prescribed VPA at a single centre. Visual field (VF), visual acuity (VA), length of treatment, liver enzymes and side effects were analysed. VF areas were defined using Goldmann VF (GVF) tracings recorded before, during and after VPA treatment using the V4e isopter for each eye. Using custom software, planimetric areas of VF were calculated. Results: Five of the patients (10 eyes) had two Goldmann VF tracings, allowing comparison between baseline and follow-up VF. After 9.8 months of VPA, VF decreased by 0.145 cm 2 (26.478%) (p=0.432). For 22 of the patients (41 eyes), VA data was available, and logarithm of the minimum angle of resolution (logMAR) score changed by 0.056 log units (representing a decline in VA) after 14.9 months on VPA (p=0.002). Twelve patients (38.7%) reported negative side effects related to VPA use. Conclusions: VPA plays a complex role in patients with pigmentary retinal dystrophies and may be associated with VA and field decline as well as adverse side effects. Physicians should use caution with using VPA for pigmentary retinal dystrophies.